Simple Fabrication of Efficient HPLC Columns Utilizing Supercritical Carbon Dioxide as a Diluent - MORI, Kenichi; TAKAHASHI, Makoto; OGINO, Kenji; HIROSE, Mikiko (KOBUNSHI RONBUNSHU, 2005)
Crosslinked porous polymers were synthesized utilizing supercritical CO2 as a diluent in a stainless steel column, using styrene (St) or methyl methacryrate (MMA) as a monomer and divinylbenzene (DVB) or ethylene dimethacryrate (EDMA) as a crosslinking agent. The polymerizations were carried out at a monomer concentration in the range from 30 to 60vol% relative to the total column volume under a pressure of 10-25MPa for 2-10 hours. The pore characteristics and the homogeneity of fabricated monolithic columns were evaluated from the elution behaviors of toluene and polystyrene standards using tetrahydrofuran as an eluent. In St-DVB systems, the monolithic column showing the high selectivity for the size exclusion separation was obtained by adjusting the polymerization conditions. In MMA-EDMA systems, it was difficult to obtain the monolithic column with the pores for the size exclusion separation, but sufficient homogeneous packing was observed. The addition of CO2-philic 2, 2, 3, 3, 4, 4, 4-heptafluoro butyl methacrylate decreased the size of particles, and increased the theoretical plate number of the column. The pores, which are necessary for the size exclusion separation, were formed by twostep polymerization in which the polymerization temperature varied from 70°C to 100°C.